A comparative study to evaluate the outcome of routine use of drain verses no drain after laparoscopic cholecystectomy: a tertiary care teaching centre experience - Chauhan, Himesh R.; Vaishnav, Umesh G. (International Surgery Journal, 2016)
Background: Laparoscopic cholecystectomy (LC) is the currently the gold standard method of cholecystectomy for symptomatic cholelithiasis. The role of routine drainage after LC to decrease postoperative morbidity is still an issue of considerable debate. This study aims to assess the benefits and harms of routine abdominal drainage and to compare the outcome of sub hepatic drainage with no drainage after uncomplicated LC. Methods: This retrospective study was conducted in two phases, as open, randomized controlled trial (RCT), conducted in general surgery department of Civil Hospital - Sola, Ahmedabad, from April 2013 to March2014 for phase I and From April 2014 to December 2014 for phase II. In this study, in phase I, total 160 patients with chronic calculus cholecystitis underwent LC. Patients were divided into two groups, sub hepatic drainage (group A: 78 patients) or no drainage (group B: 78 patients). The rest 4 patients were excluded either due to conversion or elective sub hepatic drainage. In phase II, 110 consecutive patients were enrolled, who underwent LC with No sub hepatic drainage. Results: Duration of operation, character and amount of drain fluid (if placed), postoperative ultrasound for sub hepatic collection, postoperative pain, postoperative nausea/vomiting, duration of hospital stay, and preoperative or postoperative complications were noted and analysed. Duration of operation and hospital stay was slightly longer in group A patients (P values 0.002 and 0.029, respectively); postoperative pain perception, nausea/vomiting, and postoperative complications were nearly same in both groups (P value 0.064, 0.078, 0.003, respectively). Sub hepatic fluid collection was more in group A (P=0.002). Phase II results were nearly similar to group B patients in phase I. Conclusions: Routine sub hepatic drainage after LC is not necessary in uncomplicated cases.